Consequences of using the plane stress assumption for damage calculation in crash analyses: - Walters, C.L. (2014)
Simulation of failure in plate materials (represented as shell elements) is critical for the correct determination of crash performance of ships and offshore structures. This need has traditionally been filled with failure loci that give the failure strain in terms of stress triaxiality. In recent years, a third dimension (Lode parameter) has been introduced in the form of the Modified Mohr Coulomb failure criterion and Lode parameter adjusted Gurson-type models. This development introduces ambiguity for shell structures, in which only two dimensions are represented. The typical way of addressing this is to assume that shell structures fail in plane stress, thus reducing the problem back to 2-D. However, the assumption of plane stress is violated as soon as necking begins, causing different stress triaxialities and Lode parameters than would be expected from the planar case. More importantly, the inhomogenous necked region is then homogenized over the entire shell element. In this paper, the consequences of the through-thickness plane stress assumption are assessed through a finite element model of a plate that is subjected to a far-field stress